ZIS Management and Accountability in the Era of Digitalization in West Kalimantan LAZ - Verdianti, Verdianti; Kalbarini, Rahmah Yulisa; Atiqah, Nur (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The condition of society in the digital era which is inseparable from online-based technology and social media is an opportunity for zakat amil institutions to optimize zakat and in efforts to facilitate zakat fund raising. Currently, technological advances have a positive impact on the development of zakat funds and credibility if zakat amil institutions can utilize them appropriately and consistently. Therefore, this study aims to determine zakat management and LAZ accountability in the West Kalimantan region through the use of digital-based technology. This research method uses qualitative research with content analysis. The results show that innovations in collecting zakat through digital channels have not been fully able to optimize the potential for collecting zakat funds in West Kalimantan, and most LAZs have not maximized the use of the internet and websites in providing financial information and financial reports to the public/ muzakki.